High-resolution phonocardiogram parameters; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Zemlyakov I. Yu.; Zdanov D. S.; Kosteley Y. V.; Golobokova E. V.; Dikman E. Yu. Ekaterina Yurievna; Bureev A. Sh. (2021, 2021)
Title screen